Communication Technologies, Information Security and Sustainable Development Third International Multi-topic Conference, IMTIC 2013, Jamshoro, Pakistan, December 18--20, 2013, Revised Selected Papers - Shaikh, Faisal Karim; Chowdhry, Bhawani Shankar; Zeadally, Sherali; Hussain, Dil Muhammad Akbar; Memon, Aftab Ahmed; Uqaili, Muhammad Aslam (Springer eBooks, 2014)
This book constitutes the thoroughly refereed proceedings of the Third International Multi-topic Conference on Communications, Technologies, Information Security and Sustainable Development, IMTIC 2013, held in Jamshoro, Pakistan, in December 2013. The 27 revised papers presented in this volume were carefully reviewed and selected from 140 submissions. The topics presented had a reasonable balance between theory and practice in multi-disciplined topics including wireless sensor networks, cloud computing, wireless communication, antenna design, signal processing, software engineering, image processing, bioinformatics and telemedicine, neural networks, automation and control, and green renewable energy.